Nyāyakaustubhaḥ : Pratyakṣabhāgaḥ - Mahādeva Puṇatāmbekara, fl. 1650-1700 (Princess of Wales Saraswati Bhavana texts, 1930)
Part of a 18th century treatise of the neo-Nyaya school in Indic philosophy, deals with perception (Pratyakṣa)